The Historiography of the Educational Ideal Study in the Domestic Pedagogical Theory of the XIX – the Beginning of the XX Century - Lyudmyla Yershova (Pedagogical Discourse, 2013)
The historiographical analysis of the changesin historical and pedagogical paradigm of the educational ideal as a component of the domestic educationalsystem in the XIX – early XX century is suggested. Special aspects in imaging the problem of forming the educational ideal in epistolary sources in late XVIII century and their influence on pedagogical letter writing of underrussianUkrainian intellectual elite are characterized. The development of educational ideal idea in pedagogical heritage of Kyiv School of theology teachers is grounded. Specifics in learning the problem of forming the personality ideal in modern historical-pedagogical, philosophical, historical, literary, culturological and other researches are shown. The main problems in modern state of historiography in transformation of educational personality ideal problems on Ukrainian lands of Russian Empire are revealed.